COMMUNITY KNOWLEDGE RELATIONSHIP WITH HANDLING OF SYMPTOMS OF INCREASED URIC ACID LEVELS IN KAYEE LEE VILLAGE KECAMATAN WANTING JAYA ACEH BESAR DISTRICT - Aina Fadhla; Maulida Maulida; Eridha Putra (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Gout is one of several diseases that will be a problem for sufferers because it not only interferes with health but can also cause physical disabilities. High uric acid levels in the blood exceeding normal limits cause a buildup of uric acid in the joints and other organs of the body. This buildup of uric acid makes joints ache, sore and inflamed. As humans, they must have different behaviors to deal with their illness according to the behavior they have, the behavior itself has components in which there are knowledge, attitudes, and actions. This study aims to determine the relationship between community knowledge and treatment of symptoms of increased uric acid levels in Kayee lLee Village, Wanna Jaya District, and Aceh Besar District. The design of this study will use a cross-sectional type of analytics. The population in this study were those who actively participated in the elderly Posyandu and had been diagnosed with gout as many as 32 people. The sampling technique used a total sampling technique of 32 respondents. The reason for using total sampling is because the population is less than 100. This research was conducted on June 12 - July 18, 2023, using a questionnaire sheet measurement method. Data processing was carried out using the Chi-Square test. The results showed that most of the respondents with good knowledge of handling were 18 (78.3%) respondents, and those with good knowledge but no handling were 5 (21.7%). While the majority of respondents who had sufficient knowledge with handling 1 (11.1%) respondents, and those who had sufficient knowledge but no treatment were 8 (88.9%) respondents. The results of the chi-square test p-value 0.001 (p <0.05) so that it can be concluded that Ha is accepted, indicating that there is a significant relationship between knowledge and treatment of symptoms of increased uric acid levels.